Mapeamento de QTLs e eQTLs associados à reação a “Candidatus Liberibacter asiaticus” em Poncirus trifoliata, Citrus sunki e híbridos - Soratto, Tatiany Aparecida Teixeira (Universidade Federal de São Carlos, 2017)
The Centro APTA Citros Sylvio Moreira/IAC has been conducting an extensive breeding program of citrus via directed crosses. In a previous study with Citrushuanglongbing pathosystem (HLB) held in our group, using a population obtained by hybridization between Citrus sunki and Poncirus trifoliata, differences were found in the multiplication of the bacterium Candidatus Liberibacter asiaticus (CLas), the causal agent of HLB, in the parents and in the progeny. It was observed that the rate of infection and bacterial concentration was higher in C. sunki than in P. trifoliata. Thus, it is important to deepen the studies with this genus and hybrids to increase knowledge of which mechanisms could be involved in the tolerance to HLB, considered the most important disease of citrus currently. In this sense, the objective of this study was to establish sinteny between the linkage groups of the C. sunki and P. trifoliata maps with the genome of Citrus sinensis and to map genomic regions associated to tolerance CLas bacterium through phenotypic analysis (QTLs) and gene expression (eQTLs). With the comparative analysis between maps and genome, it was observed that all the linkage groups showed synteny with reference genome chromosomes used, with the exception of the linkage group 10 of the C. sunki map. For the phenotypic data, a population of 79 F1 hybrids between C. sunki and P. trifoliata was used. The quantification of the bacterium and accumulation of starch in the leaves were evaluated after two years of inoculation with the pathogen. Through the statistical analysis of the mixed model it was possible to group the hybrids into resistant, tolerant and susceptible, being important the validation of these data in the field. The expression of 14 candidate genes related to HLB was performed in 72 hybrids of the population and used as expression data for the mapping of eQTLs. It was possible to locate nine QTLs and 52 eQTLs on the C. sunki genitor map and 17 QTLs and 40 eQTLs were found on the P. trifoliata genitor map. The overlapping eQTLs of the majority genes of QTL (phenotypic data) indicates that the genes are related to the phenotype and are probably responsive to the pathogen infection.
Mapping of QTLs and eQTLs associated with reaction the "Candidatus Liberibacter asiaticus" in Poncirus trifoliate, Citrus sunki and hybrids
Keywords: Patossistema Citros-huanglongbing (HLB); Expressão Gênica; Mapeamento Genético; Citrus - Huanglongbing Pathosystem; Gene Expression; Genetic Mapping; CIENCIAS AGRARIAS